2009
DOI: 10.1016/j.ijid.2008.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus genotype in Iranian patients with hepatocellular carcinoma

Abstract: Our results concur with other reports from Iran, all showing that genotype D is the only detectable genotype in the different clinical forms of HBV infection in this country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
3
12
0
Order By: Relevance
“…Previous findings indicated that there may be an association between the geographical distribution of HDV and HBV genotypes (38). As all reports from Iran showing that genotype D is the only detectable genotype in all clinical forms of HBV infection in this country (41, 42). It is expected that HDV genotype I was detected as predominant genotype in this study.…”
Section: Discussionsupporting
confidence: 57%
“…Previous findings indicated that there may be an association between the geographical distribution of HDV and HBV genotypes (38). As all reports from Iran showing that genotype D is the only detectable genotype in all clinical forms of HBV infection in this country (41, 42). It is expected that HDV genotype I was detected as predominant genotype in this study.…”
Section: Discussionsupporting
confidence: 57%
“…The D2 sub-genotype and G, A1, D1 and D5 sub-genotypes have been already reported from India ( 28 , 29 ). The Genotype D has been already reported in Iran ( 30 ); HBV genotype D is predominant among the Iranian neighboring countries including Afghanistan ( 31 ), UAE ( 32 ), and Pakistan ( 33 ). The remaining 108 (90%) patients were negative for occult HBV infection; however the role of occult hepatitis C virus, which requires further investigation, was not evaluated in the present study ( 34 ).…”
Section: Discussionmentioning
confidence: 95%
“…No HBV S gene sequences were submitted from Saudi Arabia, Libya, Jordan, Lebanon, Bahrain, Qatar, Oman and Kuwait that did not allow the opportunity to determine the prevalence of premature stop codon in these countries. Most of the HBV sequences were reported from Iran (31)(32)(33) and Turkey (34,35). Only a few sequences were reported from Syria, Israel and Iraq, resulting in a wide confidence interval in their estimation of S gene mutation rate.…”
Section: Discussionmentioning
confidence: 99%